Pengaruh Program Relawan Pajak, Pelatihan Pajak dan Pemahaman Terhadap Minat Mahasiswa Berkarir di Bidang Perpajakan (Studi Pada Mahasiswa Fakultas Ekonomi Se-Bali) - Ni Made Ayu Sri Putri Artini; I Nyoman Putra Yasa (Universitas Pendidikan Ganesha, 2021)
This research aims to examine the tax volunteer program, tax training and understanding of students' interest in a career in taxation among students of economic faculties in Bali. This research uses a quantitative approach with survey research methods. The sampling technique was purposive sampling, with a sample size of 185. The data sources were primary data using a questionnaire distributed online via Google forms and secondary data in the form of the number of students from the faculty of economics during the 2019/2020 academic year and the number of tax consultants. The data obtained were then analyzed using multiple linear regression analysis with the help of the SPSS program. The results of this study reveal that (1) The tax volunteer program has a positive and significant effect on student interest in a career in taxation, (2) Tax training has a positive and significant effect on student interest in a career in taxation, (3) Understanding has a positive and significant effect on interest. students have a career in taxation.